Struktur- und Prozessqualität multimodaler Schmerztherapie: Ergebnisse einer Befragung von schmerztherapeutischen Einrichtungen - Nagel, Bernd; Schiltenwolf, Marcus (Der Schmerz, 2012)
Multimodal therapy has demonstrated good clinical effectiveness in the treatment of chronic pain syndromes. However, within the German health system a comprehensive and nationwide access to multimodal therapy is not available and further improvement is therefore necessary. In order to analyze the current status of multimodal therapy and specifically its structural and procedural requirements and qualities, a survey was carried out in 37 pain clinics with established multimodal treatment programs. An anonymous questionnaire was used for data collection. Results demonstrated that a substantial accordance was found between all pain clinics concerning requirements for space, facilities and staff. Structured multidisciplinary assessments were carried out by all pain clinics even though the amount of time allocated for this varied widely. The main focus of multimodal therapy in all facilities was based on a common philosophy with a cognitive-behavioral approach to reduce patient helplessness and avoidance behavior and to increase physical and psychosocial activities as well as to strengthen self-efficacy. Some differences in the ways and means to achieve these goals could be demonstrated in the various programs.
Gesehen am 30.01.2020